High frequencies thresholds and otoacoustics emissions in patients with sickle cell anemia (Research, Society and Development, 2021)
Objective: To verify auditory thresholds at conventional and high frequencies and the presence of distortion product otoacoustic emissions in sickle cell patients, analyzing the age group variable. Method: Observational, prospective, analytical cohort for diagnostic purposes. Conventional audiometry, high frequency audiometry and distortion product otoacoustic emissions were performed in patients with the disease. Results: 38 patients were evaluated, 16 (42.1%) in the age group from 7 to 20 years old and 22 (57.9%), from 21 to 35 years old. Hearing impairment in conventional audiometry was 6.3% in the age group of 7 to 20 years and 13, 6%, between 21 and 35 years. There was no statistically significant difference between the age groups (p = 0.624). In high frequency audiometry, changes in 25% of children and adolescents and in 68.2% of adults. Adults had greater hearing loss (p = 0.021). There was no significant difference when comparing the distortion product otoacoustic emissions signal / noise ratio measurements between the ears, both in the total sample and by age group (p> 0.05). There was no significant association between the results of the distortion product otoacoustic emissions changes and hearing loss at ultra-high frequencies both in children and adolescents (p = 0.250) and in adults (p = 0.121). When comparing the sensitivity of the high frequency audiometry and distortion product otoacoustic emissions exams, there was a significant difference between them only in adults (p = 0.004). Conclusions: Adults with a longer duration of exposure to the disease showed increased thresholds in high frequency audiometry, as well as changes in distortion product otoacoustic emissions.